GAMIFICATION IN EDUCATION: ENHANCING STUDENT ENGAGEMENT AND LEARNING OUTCOMES - Nematova Mavsuma Ulugbek kizi (PEDAGOGS, 2024)
Abstract. In recent years, gamification has emerged as a popular strategy in various fields, including education. By integrating game-based elements into educational environments, educators aim to boost student engagement and enhance learning outcomes. This article explores how gamification works in education, its benefits, and practical examples of its application.